2006
DOI: 10.1097/01.rli.0000209663.00629.8a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcatheter Hepatic Arterial Embolization on Angiogenesis in an Animal Model

Abstract: TAE of hepatic tumors results in the stimulation of angiogenesis in the residual viable tumor, which could have an adverse effect on the therapeutic efficacy of TAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…In addition, several studies in other models have also implied that hypoxia caused by hepatic blood flow blockage induced angiogenesis and hence promoted malignant potential of tumors via HIF-1a activation. (11)(12)(13) Notably, obstruction of the hepatic artery induced EMT in hepatic tumor cells in our study, which would also lead to more invasive and ⁄ or metastatic phenotypes, and has been linked to the hypoxia response. (28) EMT, as one of the major biological effects of hypoxia, plays a significant role in a number of pathological states, including tumor metastasis and organic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, several studies in other models have also implied that hypoxia caused by hepatic blood flow blockage induced angiogenesis and hence promoted malignant potential of tumors via HIF-1a activation. (11)(12)(13) Notably, obstruction of the hepatic artery induced EMT in hepatic tumor cells in our study, which would also lead to more invasive and ⁄ or metastatic phenotypes, and has been linked to the hypoxia response. (28) EMT, as one of the major biological effects of hypoxia, plays a significant role in a number of pathological states, including tumor metastasis and organic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic significance of failure of blocking vessel supply is uncertain. Heightened invasion has recently been implicated as a response to hepatic artery occlusion in several animal models of orthotopic VX2, (27) walker-256, (12) and NF13762 murine breast tumor, (11) in which angiogenesis and revascularization of the tumor tissues was more distinct, and so favored intravasation of tumor cells. In this study, we introduced HAL into the human HCC orthotopic nude mouse model (using MHCC97L and HepG2 cells) and demonstrated that therapeutically efficacious blockage of the blood flow could elicit an adaptive-evasive response from hepatic tumor cells, involving an augmented invasive phenotype, with encroachment on the capsule, maligant intravasation, increased dissemination, and the emergence of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two options differ by the use of embolic agent, the time span and the amount of drug delivered to the tumor. However, this therapeutic approach suffers from two main drawbacks: first doxorubicin might not be the ideal drug for this application (3)(4)(5), second the ischemia induced by the embolization procedure contributes to the formation of new vessel sprouts, particularly in the periphery of the tumor (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%